Jurgen Habermas: Problem Dialektika Ilmu Sosial - ‘Irfaan, Santosa (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Habermas critical theory is a reconstruction effort to Frankfurt school that inspired by Karl Marx’s critical theory, thatfacing dead end. With continuing concern of his previous thinkers to radically alter practical thinking structure, Habermasformulate that concern with new and original critical theory concept. This is clear on changing process dimension, whereHabermas choosing different way from his predecessors, with non-revolutionary and non-violence. Namely, through socialtransformation, with emancipate dialogs, communicative method, without domination method